A ratiometric fluorescent nanoprobe based on terbium functionalized carbon dots for highly sensitive detection of an anthrax biomarker1. Issue 24 (25th March 2015) - Chen, Hao; Xie, Yujie; Kirillov, Alexander M.; Liu, Liangliang; Yu, Minghui; Liu, Weisheng; Tang, Yu
<x xml:space="preserve">Abstract</x> By preparing biocompatible carbon dots (CDs) that act as the scaffold and fluorescence reference, a ratiometric fluorescent nanoprobe based on Tb3+ ions functionalized CDs was designed and fabricated to detect an anthrax biomarker with high selectivity and sensitivity.